Proposta de ebook dinâmico e interativo para o ensino de função quadrática - Borba, Leonardo Costa de (2025)
This work develops a proposal for an interactive and dynamic ebook for teaching quadratic functions in high school. The proposal is based on the principles of the use of technology, interactivity, analysis of student performance in large-scale tests and recommendations based on these tests. The work discusses how the ebook was constructed and based on what methodologies it was designed and structured. As a tool for producing interactive teaching material, we use a markup language called PreTeXt, which has the necessary resources to produce interactive materials, integrating tools such as Desmos and GeoGebra. For methodological development, we took into account students’ mistakes and successes in the Paraná Test, recommendations based on PISA results, and official documents such as the BNCC and SAEB Reference Matrices, and we were inspired by Active Methodologies and guided by Bloom’s Taxonomy . With this work we present a teaching proposal for students from a generation born with technology, who do not seem to have much interest in physical books and who are used to interacting with informational content available on the internet. The proposed material is available at: https://leonardocosbor.github.io/Fun-o-Quadr-tica/minimal-2.html (click here).